Meta-Analysis of the Effect of Pelvic Floor Muscle Training in Reducing Urinary Incontinence and Elevating Quality of Life in Women - Addini, Ragil Aidil Fitriasari; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Urinary incontinence is a complaint of involuntary loss of urine and often occurs in women due to bladder dysfunction or weakened pelvic floor muscles. Pelvic floor muscle training (PMFT) is an exercise to treat urinary incontinence. This study aimed to analyze the effectiveness of pelvic floor muscle training to reduce urinary incontinence and improve quality of life in women.Subjects and Method: This was a systematic review and meta-analysis. The data was obtained through journal databases including PubMed, Science Direct, and Google Scholar by selecting articles published in 2010-2020. The keywords used were (